G. P. A. Healy papers - Healy, G. P. A. (George Peter Alexander), 1813-1894.
One letter (1857 July 20) from Healy to Robert Tyler, son of President John Tyler, regarding Healy's intention to paint a portrait of the president and thirty-seven letters (1859-1863) written by Healy to Madeleine Vinton Goddard (known as Madeleine Vinton Dahlgren after her marriage in 1865 to John Adolphus Bernard Dahlgren).
Microfilm edition available (except letter to Robert Tyler)
Microfilm produced from originals in the Manuscript Division.
Painter.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dahlgren, Madeleine Vinton, -- 1825-1898 -- Correspondence; Tyler, John, -- 1790-1862 -- Portraits; Tyler, Robert, -- 1816-1877 -- Correspondence; Artists -- United States -- Correspondence; Painters